The NCDR CathPCI Registry: a US national perspective on care and outcomes for percutaneous coronary intervention. Issue 5 (15th January 2013) - Moussa, Issam; Hermann, Anthony; Messenger, John C; Dehmer, Gregory J; Weaver, W Douglas; Rumsfeld, John S; Masoudi, Frederick A
Abstract : Aims: The NCDR CathPCI Registry collects detailed clinical, process-of-care and outcomes data for patients undergoing coronary angiography and percutaneous coronary intervention (PCI) in the USA. The registry contributes to quality of care by providing data feedback on a wide range of performance metrics to participating centres and by facilitating local and national quality improvement efforts. Interventions: No treatments are mandated, participating centres receive routine quality-of-care and outcomes performance feedback reports and access to a quality dashboard for personalized performance reports. Population: Patients undergoing cardiac catheterization and PCI are retrospectively identified. No informed consent is required, as data are anonymised. From inception in 1998, more than 12 million records have been submitted from 1577 participating US centres. Baseline data: Approximately 250 fields encompassing patient demographics, medical history and risk factors, hospital presentation, initial cardiac status, procedural details, medications, laboratory values, and in-hospital outcomes. Linkages with outside sources of data have permitted longitudinal outcomes assessment in some cases. Centre personnel enter the data into the registry, in some cases facilitated by software vendors. There are non-financial incentives for centre participation. Data completeness is noteworthy with most fields missing at rates less than 5%. A comprehensive data quality program is employed to enhance data validity. Endpoints: Main outcome measures include quality process metrics and in-hospital patient outcomes. Data are available for research by application to: http://www.ncdr.com